2014
DOI: 10.1159/000381777
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Changes Induced by a High-Fat Diet and Fish Oil Supplementation in the Skeletal Muscle of Mice

Abstract: Background/Aims: To investigate the global changes in DNA methylation and methylation of the promoter region of the peroxisome proliferator-activated receptor gamma transcript variant 2 (Pparg2) gene resulting from a high-fat diet (HFD) and/or fish oil supplementation. Methods: Fish oil, rich in omega-3 polyunsaturated fatty acids, or water was orally administered to male mice for 12 weeks. After the first 4 weeks, the animals were fed a control diet or an HFD until the end of the experimental protocol, when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
0
13
0
2
Order By: Relevance
“…; Amaral et al . ). Considering the body surface area for extrapolating the dose used in the present study to humans (Reagan‐Shaw et al .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Amaral et al . ). Considering the body surface area for extrapolating the dose used in the present study to humans (Reagan‐Shaw et al .…”
Section: Methodsmentioning
confidence: 97%
“…; Amaral et al . ). Therefore, the dosage used in the present study may be equivalent to human studies.…”
Section: Methodsmentioning
confidence: 97%
“…The CO and HF groups received water by gavage at the same volume (~50 µl, according to the BW). The FO dosage was chosen based on previous studies from our group (Amaral et al, 2015;Reagan-Shaw, Nihal, & Ahmad, 2008;de Sá et al, 2016).…”
Section: Animals and Fish Oil Supplementationmentioning
confidence: 99%
“…Several studies have shown that fish oil modulates the DNA methylation status of gene promoters. For example, in a high-fat-diet study of mice, fish oil supplementation abolished the decrease in Pparg2 promoter methylation in skeletal muscle, thereby suppressing the increase in Pparg2 expression (5). Another study has shown that EPA can decrease methylation at the CCAAT/enhancer-binding protein promoter for C/EBPβ and C/EBPδ to increase their expression in U937 leukemia cells (23).…”
Section: N-3 Pufa Dna Methylation and Histone Modificationsmentioning
confidence: 99%